Kobhung and Symbols of Power the Husband in Madura (Panoptisisme Study on Behavior Wife Husband Facing Domination) - Atiqullah Atiqullah; Syaiful Hadi (Indonesian Journal of Cultural and Community Development, 2020)
First, this study discusses the settlement in the form taneyan lanjhang, namely “kobhung” located at the western end (qibla) not only serves as a center of activity for men namely the transfer of religious values to the next generation, but also a symbol of supervision and control (Panopticon) out of the family members. Second, women in villages Madura can not escape from adhandhan, arembi ', and amassa' (self-care, childbirth or caring for the family, and cooking) as a form of devotion to her husband and family. With this condition, they did not sue even accept gracefully about his role in the household, because it has been taught for generations.